2004
DOI: 10.3200/aeoh.59.5.228-236
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Short-Term Changes in Nitrogen Dioxide and Mortality in Canadian Cities

Abstract: The association between daily variations in ambient concentrations of nitrogen dioxide (NO2) and mortality was examined in 12 of Canada's largest cities, using a 19-yr time-series analysis (from 1981-1999). The authors employed parametric statistical methods that are not subject to the recently discovered convergence and error estimation problems of generalized additive models. An increase in the 3-d moving average of NO2 concentrations equivalent to the population-weighted study mean of 22.4 ppb was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 30 publications
7
116
1
1
Order By: Relevance
“…Using the large multicity studies as an example, significant and robust associations with mortality have been observed for PM 10 (PM with an aerodynamic mass median diameter of less than or equal to 10 mm) in the National Morbidity and Mortality Air Pollution Study (NMMAPS) of 90 US cities (Samet et al, 2000, reanalyzed by Dominici et al, 2003, O 3 in 95 US communities from NMMAPS (Bell et al, 2004), NO 2 in 12 Canadian cities (Burnett et al, 2004), and SO 2 in 12 European cities ranging from Athens to Wroclaw in the APHEA project (Air Pollution and Health: A European Approach) (Katsouyanni et al, 1997). A meta analysis of 109 time-series studies published since 1985 by Stieb et al (2003) also indicated significant associations between mortality and all pollutants examined, including PM 10 , O 3 , NO 2 , SO 2 , and CO, in single-pollutant models.…”
Section: Methods Used To Distinguish Effects Of Multipollutant Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the large multicity studies as an example, significant and robust associations with mortality have been observed for PM 10 (PM with an aerodynamic mass median diameter of less than or equal to 10 mm) in the National Morbidity and Mortality Air Pollution Study (NMMAPS) of 90 US cities (Samet et al, 2000, reanalyzed by Dominici et al, 2003, O 3 in 95 US communities from NMMAPS (Bell et al, 2004), NO 2 in 12 Canadian cities (Burnett et al, 2004), and SO 2 in 12 European cities ranging from Athens to Wroclaw in the APHEA project (Air Pollution and Health: A European Approach) (Katsouyanni et al, 1997). A meta analysis of 109 time-series studies published since 1985 by Stieb et al (2003) also indicated significant associations between mortality and all pollutants examined, including PM 10 , O 3 , NO 2 , SO 2 , and CO, in single-pollutant models.…”
Section: Methods Used To Distinguish Effects Of Multipollutant Exposuresmentioning
confidence: 99%
“…In the Burnett et al (2004) study, the association between NO 2 and mortality was examined in 12 of Canada's largest cities over a 19-year time period (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999). Gaseous pollutant data were collected daily while PM measurements were taken every sixth day.…”
Section: Surrogate Measures Of Pollutant Mixturesmentioning
confidence: 99%
“…Several epidemiological studies have shown consistent associations of long-term NO 2 exposure with decreased lung function and increased risk of respiratory symptoms [Ackermann-Liebrich et al, 1997;Schindler et al, 1998;Panella et al, 2000;Smith et al, 2000;Gauderman et al, 2000Gauderman et al, , 2002. Strong associations exist between NO 2 and nonaccidental mortality in daily time series studies [Steib et al, 2003;Burnett et al, 2004;Samoli et al, 2006]. NO 2 concentrations are also highly correlated with other pollutants either emitted by the same sources or formed through complex reactions in the atmosphere [e.g., Brook et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a careful analysis of differences in the mixtures between cities, using perhaps the abovementioned types of cluster analyses in such studies as in NMMAPS (Dominici et al, 2005), the Canadian multicity studies (Burnett et al, 2004) or in APHEA (Analitis et al, 2006), may shed light on this problem. Studies in which abrupt changes in pollution have occurred in one .…”
Section: Objectives For Air Pollution Researchmentioning
confidence: 99%